Rapid detection of zoonotic Streptococcus suis serotype 2 and 14 by enzyme-activated probe fluorescence quantitative PCR method - Yaxing Su; Jiajia Meng; Mingwei Zhao; Chunling Li; Shaolun Zhai; Yan Li; Pinpin Chu; Zhibiao Bian; Kunli Zhang; Dongxia Yang; Zhiyong Jiang; Hongchao Gou; et al. (BMC Veterinary Research)
Abstract Streptococcus suis serotypes 2 and 14 are the most common zoonotic strains, but previous identification methods made distinguish these two serotypes from other S. suis serotypes difficult. To effectively prevent and control them, there is an urgent need for a highly sensitive and specific method to identify these two serotypes. In this study, a fluorescent probe was designed for the single nucleotide polymorphism site at cpsK 483 of Streptococcus suis type 2 and type 14 compared with other serotypes, and an enzyme-activated probe quantitative PCR (EA-probe qPCR) method was established for the detection of Streptococcus suis type 2 and type 14 by combining with the specific hydrolysis characteristics of the RNase H2 enzyme. The results showed that the optimal probe concentration for this method was 0.5 µM and the optimal RNase H2 enzyme concentration was 25 mU.This method showed no reactivity with genomic DNA from Streptococcus suis strains 1/2, 5, 7, 9, 23, 28, 29, and 31, confirming its high specificity. And its sensitivity can reach 18.4 CFU. In addition, 19 clinical strains of Streptococcus suis type 2 or type 1/2 were tested. The results showed 100% agreement with the gene sequencing method. In conclusion, this method can meet the needs of accurate laboratory testing of Streptococcus suis serotypes 2 and 14 and has value for clinical prevention.